Load Balancing Techniques for Efficient Traffic Management in Cloud Environment - Talasila Sasidhar; Vani Havisha; Sai Koushik; Mani Deep; V Krishna Reddy (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Cloud computing is an internet based computing. This computing paradigm has enhanced the use of network where the capability of one node can be utilized by other node. Cloud service provides access on demand to distributive resources such as database, servers, software, infrastructure etc. in pay as you go basis. Load balancing is one of the vexing issues in distributed environment. Resources of service provider need to balance the load of client request. Load balancing is adapted in order to increase the resource consumption in Data centers that leads to enhance the overall performance of system achieving client satisfaction.